New Stochastic Sensors for Simultaneous Determination of Ochratoxin A, and of Aflatoxins B1 and M1 in Food and Biological Samples - Raluca-Ioana Stefan-van Staden; Cristina Bianca Ion; Jacobus (Koos) Frederick van Staden; Catalina Cioates Negut; Ruxandra-Maria Ilie-Mihai (ECS Sensors Plus)
Three stochastic sensors based on a nanographene/ferric oxide nanoparticles matrix modified with maltodextrins I (DE 4.0–7.0), II (DE 13.0–17.0), and III (DE 16.5–19.5) can simultaneously determine mycotoxins like aflatoxin B1 (AFB1), M1 (AFM1), and OTA in coffee, milk, grape juice, and biological samples like whole blood, saliva, urine, and breast milk. The sensors’ response properties were established at two pH levels to suit sample native pH values. At pH 3.00, the sensor based on MDIII had the highest sensitivity (3.57 × 10 ^8 s ^−1 mol ^−1 l) for OTA assay, while the sensor based on MDI had the widest working concentration range (1 × 10 ^–18 –1 × 10 ^–5 mol l ^−1 ). The sensor based on MDIII had the highest sensitivity (1.45 × 10 ^10 s ^−1 mol ^−1 l) for AFB1 assay. At pH 7.40, the sensor based on MDII had the highest sensitivity (7.73 × 10 ^10 s ^−1 mol ^−1 l) for OTA assay, while the sensor based on MDIII had the widest working concentration range (1 × 10 ^–18 –1 × 10 ^–3 mol l ^−1 ). For AFB1, the sensor based on MDIII had the highest sensitivity (4.66 × 10 ^11 s ^−1 mol ^−1 l) and the wider working concentration range (1 × 10 ^–16 –1 × 10 ^–10 mol l ^−1 ). The recovery results (greater than 97.00%, RSD values below 1.00%) showed that the approach can simultaneously analyse the three mycotoxins in food and biological samples.